Reverence for life Albert Schweitzer's great contribution to ethical thought - Barsam, Ara Paul.; Oxford eBooks (Oxford : Oxford University Press, 2008)
Ara Barsam provides a new interpretation of Schweitzer's reverence and shows how it emerged from his studies of German philosophy, Indian religions, and his biblical scholarship on Jesus and Paul.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Schweitzer, Albert, -- 1875-1965 -- Ethics; Schweitzer, Albert, -- 1875-1965 -- Religion; Electronic books